Transactional Politics and Democratic Integrity in Indonesia: A Fiqh Siyasah and Regulatory Framework Perspective - Sabri Samin; Imran Anwar Kuba; Mahfuz Assiddiq; Firman Natzir; Muh. Fauzi Isnan (AJIS: Academic Journal of Islamic Studies, 2025)
This study investigates the persistence of transactional politics within Indonesia’s contemporary democratic framework and critically evaluates the phenomenon from the perspective of Islamic law. Previous studies have predominantly examined transactional politics through political science and economic approaches, with limited integration between modern democratic theory and the normative framework of fiqh siyāsah and maqāṣid al-sharī‘ah, creating a clear research gap in interdisciplinary analyses of political practices in Muslim-majority democracies. This research employs a normative legal approach grounded in library research, analysing statutory regulations, classical fiqh siyāsah literature, and contemporary studies of Indonesian electoral politics. Transactional politics is the exchange of electoral support, political loyalty, or policy influence for material benefits or strategic positions in electoral competition. The findings indicate that structural factors, including high campaign costs, patronage networks, and inconsistent enforcement of campaign finance regulations and the prohibition on political dowries, drive the persistence of transactional politics. By integrating deliberative democracy, political clientelism, and political exchange theory with Islamic legal principles, this study offers a theoretical contribution by developing an integrative analytical framework to explain and normatively evaluate transactional politics within the context of contemporary Indonesian democracy.